ANALYSIS OF THE TECHNOLOGY FOR DEVELOPING A LAND RECLAMATION PROJECT (CASE OF ZHYDACHIV PLANT MANAGEMENT OF BRICK FACTORIES LLC ON THE TERRITORY OF ZHYDACHIV TERRITORIAL COMMUNITY, STRYI DISTRICT, LVIV REGION) - Pyrih , А. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
With the establishment of territorial communities, all lands within their administrative boundaries (excluding those in state and private ownership) have been transferred to their management. Among these lands there are many plots that are unproductive, degraded, or ecologically disturbed, particularly those affected by long-term activities of mining enterprises and landfill sites, including spontaneous ones. The soils in these areas typically exhibit negative natural properties, low fertility, and unfavorable environmental conditions, which make their effective economic use for agricultural or construction purposes either extremely limited or entirely unviable. A notable example is the Western section of the Zhydachiv loam deposit, which is a clay quarry. This scientific study presents a detailed assessment of the reclamation project for the Western section of the Zhydachiv loam deposit (No. 6639), dated July 28, 2022, located within the Zhydachiv Town Council, Stryi district, Lviv region. The research outlines the stages and strategies for reclaiming disturbed lands, characterizing the process for developing the deposit and draining the pit bottom and reclaimed areas. The study also determines the volume of overburden and the rates for the removal, movement, and storage of the fertile soil layer, soil-vegetation layer, and mineral stripping layer necessary for the reclamation of the quarry bottom. Furthermore, the technology utilized for reclaiming the land disturbed by mining operations has been identified. Given the proximity of the land plot to the main waterway of the Zhydachiv territorial community - the Stryi River - it is recommended, after recultivation, to allocate this area for forestry and recreational purposes, such as health improvement, active outdoor recreation, and tourism.